2014
DOI: 10.1371/journal.pone.0091681
|View full text |Cite
|
Sign up to set email alerts
|

Visual Working Memory Capacity for Color Is Independent of Representation Resolution

Abstract: BackgroundThe relationship between visual working memory (VWM) capacity and resolution of representation have been extensively investigated. Several recent ERP studies using orientation (or arrow) stimuli suggest that there is an inverse relationship between VWM capacity and representation resolution. However, different results have been obtained in studies using color stimuli. This could be due to important differences in the experimental paradigms used in previous studies.Methodology/Principal FindingsWe exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 47 publications
2
34
1
Order By: Relevance
“…However, when there was enough exposure duration to enter the late voluntary phase, VWM precision variation would be observed either with a smaller set-size (Experiment 2) or with a longer exposure duration (Experiment 3). As we will discuss, these results and the new two-phase allocation model can further reconcile previous conflicting results (Gao, Yin, et al, 2011; He et al, 2015; Machizawa et al, 2012; Murray et al, 2012; Ye et al, 2014). …”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…However, when there was enough exposure duration to enter the late voluntary phase, VWM precision variation would be observed either with a smaller set-size (Experiment 2) or with a longer exposure duration (Experiment 3). As we will discuss, these results and the new two-phase allocation model can further reconcile previous conflicting results (Gao, Yin, et al, 2011; He et al, 2015; Machizawa et al, 2012; Murray et al, 2012; Ye et al, 2014). …”
Section: Introductionsupporting
confidence: 80%
“…Our experiments were conducted with the same procedure using identical stimuli, allowing us to make direct comparisons across experiments. In addition, most of these prior studies adopted the change detection task and thus can only indirectly infer how memory precision changed based on a single accuracy measure of performance (He et al, 2015; Machizawa et al, 2012; Murray et al, 2012; Ye et al, 2014). In our study, we used an orientation recall task and performed quantitative model fitting to separately assess the probability that a memory was stored and the precision of the memory.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that directly manipulated color resolution also found that it had no effect on the CDA (Ikkai et al, 2010; Luria et al, 2010; Ye et al, 2014) and studies that manipulated orientation resolution reported mixed results (Gao et al, 2011a,b; Machizawa et al, 2012). Note that increasing the number of relevant features within an object did not affect the CDA (Luria and Vogel, 2011a; Woodman and Vogel, 2008).…”
Section: Using the Cda To Study Vwmmentioning
confidence: 99%
“…Several studies reported that manipulating the stimulus contrast in the change detection paradigm, while resulting in an impaired behavioral performance, did not have any effect on the CDA (Gao et al, 2013; Ikkai et al, 2010; Luria et al, 2010; Ye et al, 2014). This result is significant because it reveals a dissociation between the low accuracy performance (usually taken as a marker of VWM capacity) and the intact CDA amplitude, and serves as additional evidence that the CDA does not simply reflect the task difficulty.…”
Section: The Cda As An Index Of Vwm Capacitymentioning
confidence: 99%